Концептуальные основы стратегического управления устойчивым развитием металлургического предприятия - Сталинская, Е.В.; Охтень, А.А. (Економіка промисловості, 2012)
Разработана концепция стратегического управления металлургическим предприятием для устойчивого развития, которая базируется на принятии управленческих решений на основе комплекса целевых ориентиров, сформулированных как компромисс между достижением целей собственников предприятия, стандартных финансово-хозяйственных показателей и приоритетов устойчивого развития предприятия, сформулированных с учетом отраслевых особенностей и потребностей устойчивого развития общества.
Ключевые слова: стратегическое управление, металлургические предприятия, устойчивое развитие Розроблено концепцію стратегічного управління металургійним підприємством для сталого розвитку, яка базується на прийнятті управлінських рішень на основі комплексу цільових орієнтирів, сформульованих як компроміс між досягненням цілей власників підприємства, стандартних фінансово-господарських показників та пріоритетів сталого розвитку підприємства, сформульованих з урахуванням галузевих особливостей і потреб сталого розвитку суспільства.
Ключові слова: стратегічне управління, металургійні підприємства, сталий розвиток. An aggregate representation of the interaction of an industrial enterprise, its owners, government, society and the environment in the context of sustainable development and the interconnection between enterprise’s sustainable development priorities and goals and policies of enterprise’s owners was analyzed in order to reveal the shortcomings of standard approaches and propose the ways to overcome them. The concept of strategic management of a metallurgical enterprise’s sustainable development was developed that is based on management decisions based on a set of targets that are a compromise between achieving the objectives of company owners, standard financial and economic indicators and priorities for sustainable development taking into account sectoral features and requirements of society sustainable development.
Keywords: strategic management, metallurgical enterprises, sustainable development